2017
DOI: 10.2807/1560-7917.es.2017.22.26.30565
|View full text |Cite
|
Sign up to set email alerts
|

Co-circulation of multiple subtypes of enterovirus A71 (EV- A71) genotype C, including novel recombinants characterised by use of whole genome sequencing (WGS), Denmark 2016

Abstract: In Europe, enterovirus A71 (EV-A71) has primarily been associated with sporadic cases of neurological disease. The recent emergence of new genotypes and larger outbreaks with severely ill patients demonstrates a potential for the spread of new, highly pathogenic EV-A71 strains. Detection and characterisation of these new emerging EV variants is challenging as standard EV assays may not be adequate, necessitating the use of whole genome analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…NGS methods sequencing RNA molecules directly have similar characteristics to random RT-PCR methods but with the added benefit of not requiring RT-PCR amplification steps that might introduce errors in the sequence. NGS metagenomics and target-specific techniques have been described before to obtain nucleotide sequences of EV strains present in clinical samples, either directly from the sample or from infected cell cultures ( Victoria et al, 2009 ; Yozwiak et al, 2010 ; Huang et al, 2015 ; Bessaud et al, 2016 ; Midgley et al, 2017 ; Montmayeur et al, 2017 ; Fernandez-Garcia et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…NGS methods sequencing RNA molecules directly have similar characteristics to random RT-PCR methods but with the added benefit of not requiring RT-PCR amplification steps that might introduce errors in the sequence. NGS metagenomics and target-specific techniques have been described before to obtain nucleotide sequences of EV strains present in clinical samples, either directly from the sample or from infected cell cultures ( Victoria et al, 2009 ; Yozwiak et al, 2010 ; Huang et al, 2015 ; Bessaud et al, 2016 ; Midgley et al, 2017 ; Montmayeur et al, 2017 ; Fernandez-Garcia et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, alternate approaches have been taken to sequence the full-length EV genome 26 , 33 , 34 . Tan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular investigation of EV outbreaks and asymptomatically circulating viruses found that isolates of a same type from the same area may be phylogenetically distinct and unrelated epidemiologically. [39][40][41] For example, EV-A71 genotype C4 was known to be the cause of a major epidemic in China, but a study in an isolated province showed that EV-A71 C4 was rep- even in a patient with typical clinical presentations, does not ensure an epidemiological link with an outbreak without a molecular analysis.…”
Section: Co-circulation Of Virus Variantsmentioning
confidence: 99%
“…Routine tools of the twentieth century did not distinguish viruses within a type. Molecular investigation of EV outbreaks and asymptomatically circulating viruses found that isolates of a same type from the same area may be phylogenetically distinct and unrelated epidemiologically . For example, EV‐A71 genotype C4 was known to be the cause of a major epidemic in China, but a study in an isolated province showed that EV‐A71 C4 was represented by two epidemiologically unrelated subgenotypes, C4a and C4b .…”
Section: Introductionmentioning
confidence: 99%